(untitled) (Journal of Parents and Teachers, 2025)
The article describes the Basic Curriculum Design and the sections in which it is differentiated: introduction (the newspaper, essential), blocks (the newspaper, conditioning), teaching guidelines (prominent place), and evaluation guidelines (presence of mass communication sources).